Intelligent textiles for martial arts - Tama, Derya (2017)
Martial arts have become very popular among the young population and even children, especially over the past 10-15 years. This interest has created a research field for researchers and manufacturers about martial arts' clothing and equipment, especially in terms of intelligent textiles. This study has been conducted in order to present intelligent textile products for martial arts' equipment and clothing. For this purpose, we have analyzed and presented different martial art divisions' equipment and clothes and the existing electronic systems.